2020
DOI: 10.1177/2050312120919240
|View full text |Cite
|
Sign up to set email alerts
|

Childhood hearing impairment and its associated factors in sub-Saharan Africa in the 21st century: A systematic review and meta-analysis

Abstract: Background: Childhood hearing impairment is still a significant cause of disability in the 21st century in developing countries. Particularly, the burden is more severe in sub-Saharan Africa, where the majority of children with hearing problems is living. Thre are great variations and inconsistencies of available findings conducted in sub-Saharan Africa. Hence, the aim of this review was to determine the pooled prevalence of childhood hearing impairment and its associated factors in sub-Saharan Africa. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
0
17
0
3
Order By: Relevance
“…Our study found this: 7% of students had SNHL > 20 dB and 18% of students had CHL > 20 dB in 1 or both ears, while 7% of students had an air bone gap of at least 15 dB at 2000 and/or 4000 Hz. Previous studies including meta analyses of African hearing loss 1,3,7 found sub-Saharan African children with hearing losses over 25 dB to be 7-13% 1,3,5,6,10 and over 35 dB to be 1% . 7 Sensorineural level elevations above 25 dB were 10% in the only study which determined masked bone thresholds.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our study found this: 7% of students had SNHL > 20 dB and 18% of students had CHL > 20 dB in 1 or both ears, while 7% of students had an air bone gap of at least 15 dB at 2000 and/or 4000 Hz. Previous studies including meta analyses of African hearing loss 1,3,7 found sub-Saharan African children with hearing losses over 25 dB to be 7-13% 1,3,5,6,10 and over 35 dB to be 1% . 7 Sensorineural level elevations above 25 dB were 10% in the only study which determined masked bone thresholds.…”
Section: Discussionmentioning
confidence: 96%
“…Most studies of hearing loss in Africa rely on self-assessment questionnaires, or smart phonescreeners. [1][2][3][4][5]12,13 Studies using audiometers document PTA's but often do not report masked bone levels. 4,6,7,9 A few countries appear to have access to local audiological services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HI merupakan hambatan perkembangan utama di dunia, lebih dari dua pertiga populasi masyarakat dunia mengalami HI, mayoritas dari negara berkembang. Di dunia, 466 juta orang mengalami gangguan pendengaran dan 34 juta adalah anak-anak (Chadha & Cieza, 2017); Desalew et al, 2020;lechukwu et al, 2016). Diperkirakan pada tahun 2050, lebih dari 900 juta orang akan mengalami gangguan pendengaran (Desalew et al, 2020).…”
Section: A Pendahuluanunclassified
“…A meta-analysis of studies on childhood hearing impairment between 2000 and 2018 in sub-Saharan Africa found a pooled prevalence of 10%. 1 SDQ; Nigeria found a prevalence of 13.9%. 2 According to the WHO, unaddressed hearing impairment poses an annual global cost of US$ 750 billion.…”
Section: Introductionmentioning
confidence: 99%